STRESS MANAGEMENT INTERVENTION IN CAREGIVERS OF PEOPLE WITH SCHIZOPHRENIA AT PUSKESMAS X YOGYAKARTA - Iyulen - Pebry; Mar'atul Khusna (State Islamic University (UIN) Ar-Raniry, 2023)
Being a caregiver for patients with schizophrenia is not easy. Physically, caregivers certainly experience fatigue and sometimes get sick or drop. Psychologically, caregivers experience stress, anxiety, fear and others. As for the behavior shown such as anger, aggression, apathy and others. In the social aspect, of course the caregiver feels embarrassed, cornered, threatened and many other impacts. The results of the assessment using the Subjective units of Distress Scale (1-10) conducted on 6 caregivers who visited X health center, showed stress scores that were in the medium and high categories. This was reinforced by an interview with one of the caregivers and health workers at the health center. One of the efforts to reduce the stress condition of caregivers can be through psychological intervention, namely stress management. This study aims to see the effect of stress management intervention on caregivers of people with schizophrenia. This study used a quasi-experimental approach with a one group pretest postest design. The sampling technique used purposive sampling. The results showed that there was a change in stress conditions after being given the intervention with an average decrease of 3 points.